LIQUIDITY, ASSET MANAGEMENT, AND CAPITAL STRUCTURE IN EMERGING-MARKET TEXTILE FIRMS - Rudy Syafariansyah Dachlan; Sri Wahyuti; Zahrotul Ariska (Research In Management and Accounting (RIMA), 2026)
The financial performance of textile firms in emerging markets is often constrained by difficulties in managing liquidity, optimizing assets, and structuring capital effectively. This study investigates how liquidity, asset management, and capital structure shape the performance of Indonesia's textile companies, a sector that has faced intense competition and volatility during 2019–2023. Employing a quantitative explanatory research design, panel data from six listed firms on the Indonesia Stock Exchange were analyzed using multiple regression techniques to capture the extent to which firm-level financial policies influence profitability. The findings reveal that liquidity exerts a significant negative influence, reflecting the inefficiency of excessive cash holdings or misallocated current assets. In contrast, asset management demonstrates a positive effect, underscoring the importance of efficient resource utilization in enhancing competitiveness. Meanwhile, capital structure shows a negative association, suggesting that higher leverage undermines financial stability in capital-intensive industries. Theoretically, these results validate trade-off theory, pecking order theory, and the resource-based view, while empirically clarifying contradictions in prior studies. Practically, the study offers insights for managers, investors, and policymakers in balancing liquidity, efficiency, and leverage to build resilient financial strategies in volatile markets.